PENENTUAN KUALITAS AIR DI PERAIRAN TIGARAS KECAMATAN DOLOK PARDAMEAN KABUPATEN SIMALUNGUN (Determination of Water Quality in Waters Tigaras of District Dolok of Pardamean, Simalungun) - Luly Nanda Arista; Budi Utomo; Zulham Apandy Harahap (AQUACOASTMARINE, 2017)
Tigaras waters is one of Lake Toba area which is used as a tourist area, ferry ports and floating net cage aquaculture activities which could effect water quality in Tigaras. The research to determine the value of the parameter of physic, chemistry, biology and water quality based on the quality standard PP RI No. 82/2001 on water quality management and water pollution control. This research was done on June to July 2016. The study used purposive random sampling method. There were four first station (port), the second station (cages), the third station (tourist), and fourth station (control). Value parameter of physics, chemistry and biology, among others temperature 26oC–29oC, TSS 54-56 mg/l, TDS 25-27,5 mg/l, brightness 180-198 m, pH 7,2-7,65, DO 5,35-6,45 mg/l, BOD 0,9-2,85 mg/l, COD 2,812-8,90565 mg/l, nitrate 0,5 mg/l, phosphote 0,19-0,51 mg/l, total coliform 65,9–2505 MPN/100ml. Water quality based on standard class one and class two is being polluted with respective value are -25 and -15, while based on standard class three is not polluted or meet quality standard value.Keywords : water quality, Storet method, Tigaras waters